Cerebral venous sinus thrombosis related to vaccine-induced immune thrombotic thrombocytopenia: First reported case in Vietnam - Hai, Hoang Bui; Phuc, Do Giang; Chung, Nguyen Thanh; My, Tran Thi Kieu; Xuan, Le Thi Thanh; Dinh , Michael D; Hieu, Nguyen Lan (Tạp chí Nghiên cứu Y học, 2021)
Vaccination remains one of the most important public health interventions to control and mitigate the impacts of COVID-19 worldwide. A number of post-vaccination reactions have caused concern and are the cause of vaccine hesitancy. Vaccine-induced immune thrombotic thrombopenia (VITT) has been reported in several countries such as Norway at a rate of 1 per 26000 doses of the ChAdOx1 nCoV vaccine (AstraZeneca), 15 per 8 million doses of Ad26.COV2.S (Janssen; Johnson & Johnson) vaccines in the US. In Vietnam, 11.5 million doses of AstraZeneca vaccine have been administered since the commencement of a nation-wide vaccination program five months ago. We report the first case of cerebral venous thrombosis related to VITT which was promptly diagnosed and successfully treated with rivaroxaban alone. Thus, VITT is very rare in Vietnamese people vaccinated with the AstraZeneca vaccine in the prevention of COVD-19 infection.